ANÁLISE UNI E MULTIVARIADA NA DETECÇÃO DA VARIABILIDADE GENÉTICA EM GIRASSOL - Schwertner, Diogo V.; Martins, João A. K.; Gaviraghi, Fernando; Mattioni, Tânia C.; Fontaniva, Cristiano; Matter, Edegar; Antonow, Diovani; Carbonera, Roberto; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo